2018
DOI: 10.1016/j.scitotenv.2017.10.091
|View full text |Cite
|
Sign up to set email alerts
|

From headwaters to estuary: Distribution and fate of halogenated flame retardants (HFRs) in a river basin near the largest HFR manufacturing base in China

Abstract: With the gradual phasing out of polybrominated diphenyl ethers (PBDEs), market demands for alternative halogenated flame retardants (HFRs) are increasing. The Laizhou Bay area is the biggest manufacturing base for brominated flame retardants (BFRs) in China, and the Xiaoqing River is the largest and most heavily contaminated river in this region. Water and sediment samples were collected from the headwaters to the estuary of the Xiaoqing River to investigate the distribution and fate of HFRs [i.e., PBDEs, alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 47 publications
3
50
2
Order By: Relevance
“…The PBDE concentrations reported in this study were comparable to those in sediments from four bays in Northern China (Zhen et al, 2016), Yangtze River Delta, East China (Zhu et al, 2013), and Western Arctic Ocean (Cai et al, 2012). This study reported values much lower than the Xiaoqing River in China (Zhen et al, 2018), three bays in South America (Baron et al, 2013), and Llobregat river, Spain (Baron et al, 2014). For aBFRs, the levels in this study were higher than those found in Yangtze River Delta, East China (Zhu et al, 2013), three bays in South America (Baron et al, 2013), and Western Arctic Ocean (Cai et al, 2012), but lower than those in four bays in North China (Zhen et al, 2016), Llobregat river, Spain (Baron et al, 2014), and Xiaoqing River, China (Zhen et al, 2018).…”
Section: Concentration and Comparison Of Hfrs In The Sedimentssupporting
confidence: 75%
See 2 more Smart Citations
“…The PBDE concentrations reported in this study were comparable to those in sediments from four bays in Northern China (Zhen et al, 2016), Yangtze River Delta, East China (Zhu et al, 2013), and Western Arctic Ocean (Cai et al, 2012). This study reported values much lower than the Xiaoqing River in China (Zhen et al, 2018), three bays in South America (Baron et al, 2013), and Llobregat river, Spain (Baron et al, 2014). For aBFRs, the levels in this study were higher than those found in Yangtze River Delta, East China (Zhu et al, 2013), three bays in South America (Baron et al, 2013), and Western Arctic Ocean (Cai et al, 2012), but lower than those in four bays in North China (Zhen et al, 2016), Llobregat river, Spain (Baron et al, 2014), and Xiaoqing River, China (Zhen et al, 2018).…”
Section: Concentration and Comparison Of Hfrs In The Sedimentssupporting
confidence: 75%
“…This study reported values much lower than the Xiaoqing River in China (Zhen et al, 2018), three bays in South America (Baron et al, 2013), and Llobregat river, Spain (Baron et al, 2014). For aBFRs, the levels in this study were higher than those found in Yangtze River Delta, East China (Zhu et al, 2013), three bays in South America (Baron et al, 2013), and Western Arctic Ocean (Cai et al, 2012), but lower than those in four bays in North China (Zhen et al, 2016), Llobregat river, Spain (Baron et al, 2014), and Xiaoqing River, China (Zhen et al, 2018). These results indicated a relatively moderate level of contamination at the sites studied herein.…”
Section: Concentration and Comparison Of Hfrs In The Sedimentscontrasting
confidence: 60%
See 1 more Smart Citation
“…To study the distribution and contamination of PAHs in the Xiaoqing River, sediment and water samples were collected from 30 sites in April, 2014. Details of the sampling strategy and stations can be found in previous publications (Jiang et al 2017) (Zhen et al 2018). Here, we provide a brief introduction.…”
Section: Sample Collectionmentioning
confidence: 99%
“…For example, a chemical plant, Shandong Tiancheng Biotechnology Co., Ltd., with an annual production of 15,000 tonnes of chlorpyrifos, is located at Zibo. Our previous studies have shown that the Xiaoqing River is seriously polluted by certain emerging contaminants, such as perfluoroalkyl carboxylic acids and brominated flame retardants (Heydebreck et al, 2015;Zhen et al, 2018b). However, little is known about the situation concerning CUPs in this area, especially in the Xiaoqing River; this is an important issue because CUPs are widely applied in this region.…”
Section: Introductionmentioning
confidence: 99%